Conceptual framework of good management from the Islamic perspective - Abdullah @ Chuah Hock Leng, Osman; Ishak, Mohd. Shuhaimi (The Social Sciences Research Society, 2012)
Conceptual framework of good management from the Islamic perspective Good management is the most important competitive factor for any business organization. Making oneself and others succeed is one of the crucial aspects of good management because it is the mechanism of planning, organising, leading and controlling the entire organs of a business organisation. The purpose of this paper is to develop a conceptual framework of good management based on the Islamic principles, not only to ensure success in the running of the business but at the same time making sure that the moral and ethical values of Islam are observed. This paper endeavours to look into the sources of Islam while extracting other sources of the modern approach of management. As a result, the management practices are handled according to the social-economic fabrics of Islam whose suitability is relevant for modern day business operations